Diversity and community structure of rhizosphere bacteria in shallot treated with Rhizophagus intraradices and Trichoderma asperellum - HERTINA ARTANTI; TRI JOKO; SURYANTI SURYANTI (Society for Indonesian Biodiversity, 2023)
Abstract. Artanti H, Joko T, Suryanti. 2023. Diversity and community structure of rhizosphere bacteria in shallot treated with Rhizophagus intraradices and Trichoderma asperellum. Biodiversitas 24: 6248-6255. The rhizosphere is an area rich in nutrients and has high microbial activity. The condition of the rhizosphere area can influence plant growth and resistance to pathogens. This study aimed to determine the effect of the application of Rhizophagus intraradices and Trichoderma asperellum on the diversity and community structure of shallot rhizosphere bacteria as well as on the growth and health of shallots. Metagenomic analysis of the shallot rhizosphere was used to determine the diversity and structure of the bacterial community in shallots treated with R. intraradices, T. asperellum, control, and bulk soil. The results showed that the application of R. intraradices and T. asperellum affected the composition and diversity of rhizosphere bacteria and the number of rhizobacteria species. The structure of rhizosphere bacteria was not affected by the application of these two fungi. The diversity and number of rhizosphere bacterial species were able to increase plant growth and resistance, especially triggered by R. intraradices.